Stock Market Integration among Asian Economies in a Case of India, China and Japan - Bhullar*, Pritpal Singh (Universitas Prasetiya Mulya, 2019)
Globalization has opened the door for global investors to avoid the saturation of investment opportunities in the domestic market. Latest technological advancement, accessibility to financial and global information, liberalization and globalization put the global market into a new investment framework. The present paper aims to examine the level of cointegration between three big Asian economic powers India, China and Japan. Twenty-years data has been analyzed by applying Johansen Cointegration, Vector Error Correction Model, and other econometric statistical tests in E-Views. The findings suggest a long-run relationship between India (BSE) and Japan Stock indices (Nikkie), but no such integration find of these two stock indices with China Stock Exchange (Shanghai).Keywords:Asian Economies, Stock Indices, VECM, Johansen Cointegration Test, E-Views*University Business School, Maharaja Ranjit Singh Punjab Technical University, Dabwali Rd, Lal Singh Nagar, Bathinda, Punjab 151001, India. https://doi.org/10.21632/irjbs.12.2.137-143